An easy-to-use baseline scoring system to predict response to peginterferon alfa-2a in patients with chronic hepatitis B in resource-limited settings. Issue 8 (November 2018) - Lampertico, Pietro; Messinger, Diethelm; Oladipupo, Hameed; Bakalos, Georgios; Castillo, Marco; Asselah, Tarik
Background: Approximately one-third of patients have durable responses after finite (48-week) treatment with peginterferon alfa-2a. The ability to identify patients likely to respond would be particularly useful in resource-limited settings. Methods: Data from 1, 363 peginterferon alfa-2a recipients (955 hepatitis B 'e' antigen [HBeAg]-positive and 408 -negative) in six studies were analysed. Baseline scoring systems were developed using generalized additive models and multiple logistic regression analysis to predict virological response (VR; HBV DNA <2, 000 IU/ml), alone or combined with alanine aminotransferase (ALT) normalization (CR) at 24 weeks post-treatment. Results: Based on the final models, points were assigned for age ≥45 (0) or <45 years (1); male (0) or female (1); hepatitis B surface antigen (HBsAg) >25, 000 (0), >7, 500-≤25, 000 (1), >1, 250-≤7, 500 (2) or ≤1, 250 IU/ml (4); HBV DNA >5 (0) or ≤5 log10 IU/ml (2) and ALT ratio >1-7 (0) or either ≤1 or >7 (1). Higher total scores (range 0-9) indicate higher likelihood of response. VR and CR rates were 28.5% (388/1, 363) and 24.4% (332/1, 363), respectively, and increased with increasing score: score 0-1 ( n =257), VR 14.8%, CR 12.8%; score 2-3 ( n =711), VR 23.1%, CR 20.1%; score ≥4 ( n =395), VR 47.1%, CR 39.5%. Conclusions: An easy-to-use baseline scoring system for use in settings where HBeAg status and HBV genotypes are unavailable would allow clinicians to identify patients with a low or high chance of achieving a durable post-treatment response to peginterferon alfa-2a. The tool can be used to inform treatment decisions in resource-limited settings.